A mass balance study of [14C]SHR6390 (dalpiciclib), a selective and potent CDK4/6 inhibitor in humans - Zhang, Hua; Yan, Shu; Zhan, Yan; Ma, Sheng; Bian, Yicong; Li, Shaorong; Tian, Junjun; Li, Guangze; Zhong, Dafang; Diao, Xingxing; Miao, Liyan (Frontiers in Pharmacology, 2023)
SHR6390 (dalpiciclib) is a selective and effective cyclin-dependent kinase (CDK) 4/6 inhibitor and an effective cancer therapeutic agent. On December 31, 2021, the new drug application was approved by NMPA (National Medical Product Administration). The metabolism, mass balance, and pharmacokinetics of SHR6390 in 6 healthy Chinese male subjects after a single oral dose of 150 mg [14C]SHR6390 (150 µCi) in this research. The Tmax of SHR6390 was 3.00 h. In plasma, the t1/2 of SHR6390 and its relative components was approximately 17.50 h. The radioactivity B/P (blood-to-plasma) AUC0-t ratio was 1.81, indicating the preferential distribution of drug-related substances in blood cells. At 312 hours after administration, the average cumulative excretion of radioactivity was 94.63% of the dose, including 22.69% in urine and 71.93% in stool. Thirteen metabolites were identified. In plasma, because of the low level of radioactivity, only SHR6390 was detected in pooled AUC0-24h plasma. stoolSHR6390 was the main component in urine and stool. Five metabolites were identified in urine, and 12 metabolites were identified in stool. Overall, faecal clearance is the main method of excretion.